Making a positive internet through Socmed Agawe Guyub - Fitrah Fasyanabilla Lotan (International Journal of Communication and Society, 2019)
This peper aims to find out the efforts of the Yogyakarta government to teach internet positive to all citizens.  The methodology of this study uses descriptive qualitative methods with a case study approach, this research uses analysis of literature and media. Media literacy is the answer to problems and concerns about provocative and negative information or messages that are now circulating among the public. Technological progress certainly does not always have a positive effect on society. Socmed agawe guyub become primer program for indonesians specially Yogyakarta can be more active to selected the infornation in social media and share only a good and right information in their social media.